(NpRAKTIKUM PO TEORETI^ESKOJ GRAMMATIKE (B((NNA ANGLIJSKOM QZYKE(B) :s (Nu^EBNOE POSOBIEs - (NmOROHOWSKAQ(B, (N|MILIQ qKOWLEWNA(B.s ((Nl(B. :s (NpROSWE]ENIE(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1973)
(NbIBLIOGR(B.: (NS(B. 178-180s
Keywords: (NaNGLIJSKIJ QZYKs -- (NiSTORIQs